PENGARUH TEMPERATUR DAN WAKTU AUSTEMPER TERHADAP SIFAT MEKANIK DAN STRUKTUR MIKRO BAJA AISI 1045 - Fahmi Deniyasa; Budi Santoso; Novi Laura Indrayani (Jurnal Ilmiah Teknik Mesin, 2018)
AISI 1045 carbon steel is being used as the main raw material vehicle engine components such asshafts, spur gears, pistons and connecting rods. Spur gear is one component that experiences themost wear and tear caused by the properties of hardness and wear resistance are poor. The impactof the spur gear wear becomes damaged and does not function normally. To minimize wear of thenecessary process of hardening heat treatment at a temperature of 845˚C was detained for 60minutes, then quenching with brine and continued with the process of austempering at 295˚Ctemperature variation, 330˚C, and 365˚C and the holding time 30 minutes, 60 minutes and 90minutes. Use the specimen 1 which is raw material of AISI 1045 steel as the compare resultswithout heat treatment. Tests conducted is hardness test, test microstructure and wear-resistanttest. The test results showed increased to 200 HB hardness of HB 182 initially, rose by 9.89% onthe specimen number 3. Testing of wear showed the lowest yield value of 5.5643747 abradedmaterial volume mm3 / mm and a specific wear value of 0.006603292 mm2 / Kg in the specimenNo. 3. Changes occur on the microstructure of ferrite and perlite into martensite and bainitemicrostructure after heat treatment in this study.